FOREIGN EXCHANGE MARKET PRESSURE INDEX AND MONETARY POLICY IN IRAQ - Hamad Khalaf, Ammar (Economic Annals, 2018)
This paper’s aims are to adequately measure a foreign exchange market pressure index that can be used to discover pressures in the Iraqi foreign exchange market early on, and to examine the effect of monetary policy intervention in the Iraqi foreign exchange market. The modelling approach used is Autoregressive Distributed Lag (ARDL), with monthly time series data spanning 2013–2017. The index used in this paper was able to identify different periods of pressure in the Iraqi foreign exchange market. In addition, the econometric analysis found that the traditional proxies for monetary policy intervention in the foreign exchange market, such as domestic credit and money multiplier, were ineffective in the case of Iraq. The results show that the Central Bank of Iraq (CBI) relied extensively on foreign reserves to mitigate pressures in the foreign exchange market. Due to the nature of the Iraqi economy and where the main source of foreign currency is oil exports, the CBI adopted a fixed exchange rate regime to control inflationary expectations and stabilize the foreign exchange market.